2017
DOI: 10.1371/journal.pone.0181330
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with foreign cultural paradigms: A systematic review on intercultural challenges of international medical graduates

Abstract: ObjectivesAn increasing number of International Medical Graduates (IMG), who are defined to be physicians working in a country other than their country of origin and training, immigrate to Western countries. In order to ensure safe and high-quality patient care, they have to take medical and language tests. This systematic review aims to (1) collect all empiric research on intercultural communication of IMGs in medical settings, (2) identify and categorize all text passages mentioning intercultural issues in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 55 publications
3
33
0
5
Order By: Relevance
“…It was also felt that many of the residents came from a culture with a more defined hierarchy and either fear of reporting superiors or feeling that this showed a lack of respect was a possible contributing factor. On literature review, this is in line with a recent systematic review of 47 studies which concluded that IMG’s faced difficulties with a loss of status and less defined hierarchies with respect to their patients, staff and supervisors as compared to home countries [14]. As far as we are aware, no studies had looked at the cultural background of residents with respect to safety event reporting.…”
Section: Introductionsupporting
confidence: 67%
“…It was also felt that many of the residents came from a culture with a more defined hierarchy and either fear of reporting superiors or feeling that this showed a lack of respect was a possible contributing factor. On literature review, this is in line with a recent systematic review of 47 studies which concluded that IMG’s faced difficulties with a loss of status and less defined hierarchies with respect to their patients, staff and supervisors as compared to home countries [14]. As far as we are aware, no studies had looked at the cultural background of residents with respect to safety event reporting.…”
Section: Introductionsupporting
confidence: 67%
“…International medical graduates made substantially fewer MELDs than those who graduated from a Swiss university and when they made an MELD, they less often reported shared decision-making with the patient and/or their relatives. International medical graduates may be less familiar with shared decision-making and patient-centered care [ 25 ]. At the time of the survey, 29% of all physicians in Switzerland were international graduates, with almost 60% of them originating from Germany [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…21,37,38 Sharing clinical information with a patient and family and taking consent may vary between countries and cultures, shaped by laws and need to be addressed early in a doctor's career. 39 Working effectively within teams, now an almost universal practice, is more complex than it at first appears. Decisions are best made when all necessary information is available, which in turn is possible only when the consultant invites even the most junior members to contribute.…”
Section: Clinical Educational and Work-culture Challengesmentioning
confidence: 99%